PELESTARIAN TRADISI DI BEMBENG PADA RITUAL PERKAWINAN MASYARAKAT BANGKALA BARAT, KABUPATEN JENEPONTO - Arya, Nosakros Arya; Jauza, Assa; Tamarah, Dinda Aisyah; Shafier, Arka Aruna (Departemen Ilmu Komunikasi, Fakultas Ilmu Soal dan Ilmu Politik. Universitas Pejuang Republik Indonesia, 2022)
One of the local traditions in Jeneponto Regency is the Di Bembeng tradition. Bembeng is a tradition used by kings or karaeng ('karaeng' the term used in the Makassar Bugis tribe) when their families are getting married. Where the bride from the karaeng will be Bembeng from a distance of approximately 100 meters from her house to the front of her house using a special place or tool that is indeed used to lift the bride and groom. The tools used in carrying out the Bembeng tradition are called Bembengang. The Bembeng tradition in the community wedding procession in West Bangkala sub-district underwent a transformation because it was also influenced by the mindset of teenagers who were around the environment, who seemed not to care about the Bembeng tradition in the environment where they lived, this is of course due to also because of the influence or impact of modernization which is increasingly affecting their mindset so that they think that the Bembeng tradition is no longer important, and most teenagers today are more inclined to follow the modernization era than the traditions that exist in their own region. When in fact it is this tradition that must be upheld and cared for because this tradition is the legacy of our ancestors who have an important role and have a high position because it is this tradition that makes us different and unique from other societies. Therefore it is very important to maintain and preserve the traditions that are in Bembeng at community wedding processions in West Bangkala sub-district. The aim of the study was to find out the meaning of the Di Bembeng tradition in the wedding procession of the people of West Bangkala, Jeneponto Regency; understand and know the forms of change from the Bembeng tradition to the wedding procession of the people of West Bangkala, Jeneponto Regency; understand and know the factors that cause the transformation of the Bembeng tradition in community marriage processions in West Bangkala sub-district, Jeneponto Regency. This research method uses a qualitative descriptive approach through a review of literature and interviews with several informants. The location of this research is in West Bangkala District, Jeneponto Regency, South Sulawesi Province. The results of the research show that the Di Bembeng tradition has undergone a transformation due to the times and changes in tradition in terms of ways and customs and the results of this research will be published in the Kareba journal at Hasanuddin University.